“Winners” and “Losers” of the Bivalve Evolution - Jasenka Sremac; Marija Bošnjak (Diversity)
Bivalves are nowadays represented by several thousand species of variable sizes and shapes. Additionally, thousands more species occurred during their 500-million-year long evolution. Present on Earth since the Cambrian, the class Bivalvia experienced periods of gradual evolution, interspersed with periods of rapid changes. Some groups of bivalves, namely clams, oysters, scallops, and marine mussels, managed to survive a series of extinctions, and their descendants still thrive in modern oceans and seas. Other groups, such as the rudists, completely disappeared from marine environments, after undergoing successful evolutionary radiation. In this study, we consider the possible reasons for the longevity of some bivalve orders and discuss the possible causes of demise of several once-successful clades. As expected, a small body size, large number of specimens, infaunal mode of life, motility, and long-living planktonic larvae proved to be evolutionary advantages during stress periods. The ability to harbor chemosymbionts could be an additional benefit during biotic crises.